Intestinal failure in gastrointestinal fistula patients. Issue 2 (February 2021) - Limb, Christopher; Read, James
Abstract: Intestinal failure is broadly understood as the failure of the gut to achieve adequate absorption of macronutrients and/or fluids and electrolytes. Enterocutaneous fistula, an abnormal connection between the gastrointestinal tract and skin, is one aetiology for intestinal failure. In this article we explore the critical knowledge within a clear framework for managing this challenging condition. We expand on the role of the multidisciplinary team and specialized tertiary centres to enhance the clinical application of this knowledge in practice. Throughout this article we highlight specific tips and pitfalls in the management of these patients.